Ще раз про залізообробне виробництво на Кам’янському городищі - Завьялов, В.І.; Терехова, Н.М. (Археологія, 2017)
Статтю присвячено залізообробному виробництву у найбільш яскравому центрі скіфського періоду Північної Євразії Камянському городищі. Зокрема подаються дані археометалографічних досліджень матеріалів пам’ятки, що дозволить зрозуміти процес формування ремесла у кочових народів. The Scythian period has a special significance in history of iron-working production development in Northern Eurasia. At that very time, iron becomes usual in everyday life of the local population. At a context of general history of iron-working craft development, the steppe nomadic population’s transfer to a settled life played a significant role. Kamianka hill-fort is the most prominent centre of this period in the Steppe Scythia. Archaeometallographic investigation of the materials from the site allow the authors to understand the process of this craft’s development by the nomadic peoples in the period of their transfer to the settled way of life. The data presented testifies that the nomads’ contacts with the bearers of technological knowledges played a key role in this process. Особое значение в истории развития железообрабатывающего производства Северной Евразии занимает скифский период. Именно в это время железо начинает входить в повседневный быт местного населения. В контексте общей истории развития железообрабатывающего ремесла существенную роль сыграл переход кочевого степного населения к оседлости. Наиболее ярким центром этого периода в степной Скифии является Каменское городище. Археометаллографические исследования материалов памятника позволяют понять процесс формирования ремесла у кочевых народов в период перехода к оседлому образу жизни. Приведенные данные свидетельствуют, что ключевую роль при этом играют контакты номадов с носителями технологических знаний.